The advantages of arbitration over litigation: an application to franchise contract - Yakub, Adamu Mahmud (2016)
Franchise disputes differ from other commercial disputes. One of the main objectives of the franchise business is to protect the honesty of the franchise structure and the franchisor’s product which are the cornerstones of the business. At the same time, the franchise relationship is also paramount to the business model, and there is a strong encouragement to ensure that any disputes between the franchisor and the franchisee are resolve in a way that produces little interruption to the franchise business as possible. Many franchisors also carry on business in more than one jurisdiction. This article examines the advantages of arbitration over litigation as a mechanism for resolving franchise disputes. Since franchise agreements are usually, if not solely, prepared by franchisors with little or no involvement from the franchisees.